Neutron dosimetry at HK-1 beam line of LVR-15 reactor for biomedical sample irradiations - Kalamara, Antigoni; Georgiou, Sofia; Stefanopoulos, Konstantinos L.; Stamatelatos, Ion E.; Kalef-Ezra, John A.; Vinš, Miroslav; Klupák, Vit; Rabochová, Michaela; Šoltés, Jaroslav; Theodossiou, Theodossis (HNPS Advances in Nuclear Physics, 2024)
The HK-1 neutron beam line at the LVR-15 reactor in ÚJV Řež, Czech Republic, was used for in vitro cell studies carried out in the framework of the FRINGE project, aiming on the development of a novel neutron capture therapy technique using Gd containing compounds. The neutron fluence rate close the HK-1 beam exit was experimentally assessed. Neutron fluence rate data were combined with Monte Carlo simulations performed using the MCNP 6.1 code, to model a well-type vial containing a thin layer of cells, with and without Gd, as well as the supporting media. Aim of the study was to evaluate the energy deposited by the neutrons in the cell monolayers and delineate the contribution of the various dose components in an attempt to interpretate the findings of the in vitro studies.